Speciation of mercury in environmental water samples with seasonal change. - Rahman, Md. Mokhlesur; Mohd Yusof, Alias (Trans Tech Publications, Switzerland, 2011)
Mercury concentrations and speciation were determined in surface water samples taken from rivers in the vicinity of industrial area, in Johore Malaysia. Samples were collected from the same sites before and immediately after rainfall. The aim of this study is to assess the influence of seasonal change in river water on the concentration of mercury (Hg) species. Trace concentrations of mercury in water samples were determined by a method involving a simple and rapid procedure involving the flow-injection inductively coupled plasma mass spectrometry (FI-ICP-MS) and graphite furnace atomic absorption spectrometry (GFAAS) techniques. Mercury vapor, generated by sodium borohydride as the reductant, was stabilized by potassium dichromate (K2Cr2O7), then released by controlled heating and detected by FI-ICP-MS. Methyl mercury (II) was preconcentrated using the ammonium pyrolidindithiocarbamate (APDTC)-chloroform extraction procedure and the chloroform extract was introduced into the graphite tube. The absolute detection limits were found to be 0.204 μg L-1 and 0.273 μg L-1 for total mercury and methyl mercury respectively, with thevariability being lower than 5% relative standard deviation (RSD) at the 5 μg L-1 level. Because of the high stability of MeHg (II)-APDTC complexes, it is possible to evaporate the extract in order to obtain a crystalline powder to be dissolved with a few micro liters of chloroform enacting MeHg (II) and Hg (II) can be detected at sub-nanogram levels.